2023
DOI: 10.15584/ejcem.2023.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Impact of face mask use during the non-stress test in pregnancy

Abstract: Introduction and aim. Face masks used to protect against the COVID 19 pandemic have become a daily routine. The aim of this study was to examine the possible effects of mask use on non-stress test (NST) results during pregnancy. Material and methods. A total of 951 pregnant women were included in the study. They were divided into two groups as those who wear masks and those who do not. These pregnant women were also divided into subgroups as preterm and term periods. Results. The mean age of the pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…A previous study on pregnant women has shown that wearing a facemask at rest did not significantly reduce arterial oxygen saturation (SPO 2 ) and heart rates when compared with non-pregnant controls [ 7 ]. Another study also found that wearing surgical facemasks during a nonstress test for fetal surveillance did not significantly affect fetal parameters, such as heart rate reactivity, variability, and decelerations [ 8 ]. However, data on the effects of surgical and N95 masks on ambulating pregnant women are either lacking or inconclusive and deserve further randomized studies.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study on pregnant women has shown that wearing a facemask at rest did not significantly reduce arterial oxygen saturation (SPO 2 ) and heart rates when compared with non-pregnant controls [ 7 ]. Another study also found that wearing surgical facemasks during a nonstress test for fetal surveillance did not significantly affect fetal parameters, such as heart rate reactivity, variability, and decelerations [ 8 ]. However, data on the effects of surgical and N95 masks on ambulating pregnant women are either lacking or inconclusive and deserve further randomized studies.…”
Section: Introductionmentioning
confidence: 99%